Classical problem about an elastic sphere with a spherical inclusion - Nikolaev, Oleksii Georhiiovych; Skitska, Mariia Viktorivna (Національний технічний університет "Харківський політехнічний інститут", 2025)
For the first time, an exact analytically justified solution of the second axisymmetric boundary value problem of the theory of elasticity in the general formulation for a sphere with a concentric spherical inclusion has been obtained using the conventional Fourier method. In the scientific works of the classics of natural science of the 19th and 20th centuries, M. G. Lame, W. Thomson, C. Somigliana, V. Cerruti, B. G. Galerkin, G. Fichera, A. I. Lurie, E. Strenberg, and A. F. Ulitko, elastic problems for a solid sphere, space with a spherical cavity, and a sphere with a concentric spherical cavity were solved in various formulations. But even these problems were not strictly justified. The problem considered in this report is much more complex, since it is associated with the conjugation of displacement and stress fields at the inclusion boundary. That's probably why it wasn't considered before. The justification for solving such a problem and establishing its solvability class using the usual Fourier method is based on the analysis of a solvable algebraic system of the sixth order with coefficients that depend on five independent continuous parameters and one discrete one. The general solution of the problem is given in the form of series in terms of axisymmetric vector basis solutions of the Lamé equation for a sphere, constructed by the authors in one of the previous articles. After transitioning to stresses and satisfying the boundary conditions, a resolving system of the above form is obtained. When analyzing the system, a lower estimate of the modulus of its determinant was first found, from which follows not only the unique solvability of the system, but also estimates of the solutions of the system itself. Уперше звичайним методом Фур’є отримано точний аналітичний обґрунтований розв’язок другої осесиметричної крайової задачі теорії пружності в загальній постановці для кулі з концентричним сферичним включенням. У наукових працях класиків природознавства 19 і 20 століть M. G. Lame, W. Thomson, C. Somigliana, V. Cerruti, B. G. Galerkin, G. Fichera, A. I. Lurie, E. Strenberg, А. Ф. Улітко розв’язувалися пружні задачі для суцільної кулі, простору зі сферичною порожниною і кулі з концентричною сферичною порожниною в різних постанов- ках. Але навіть ці задачі не було строго обґрунтовано. Задача, яка розглядається в цій статті, значно складніша, оскільки пов’язана зі спря- женням полів переміщень і напружень на межі включення. Тому, мабуть, її раніше не розглядали. Обґрунтування розв’язку подібної задачі та встановлення її класу розв’язності звичайним методом Фур’є базується на аналізі розв’язувальної алгебраїчної системи шостого порядку з коефіцієнтами, які залежать від п’яти незалежних неперервних параметрів і одного дискретного. Загальний розв’язок задачі подається у ви- гляді рядів за осесиметричними векторними базисними розв’язками рівняння Ламе для кулі, побудованими авторами в одній з попередніх статей.
Класична задача про пружну кулю зі сферичним включенням
Keywords: elastic sphere; spherical inclusion; Fourier method; field conjugation; resolving system; solvability class; external load vector; пружна куля; сферичне включення; метод Фур'є; спряження полів; розв'язувальна система; клас розв'язності; вектор зовнішнього навантаження